2009
DOI: 10.1684/ecn.2009.0146
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of tumor markers, chemokines, and metastasis-related molecules in serum

Abstract: There is a growing interest in the role that cancer biomarkers, metastasis-related molecules, and chemokines may play in the development and progression of various cancers. However, few studies have addressed the reliability of such biomarkers in healthy individuals over time. The objective of this study was to investigate the temporal reliability of multiple proteins in serum samples from healthy women who donated blood over successive years. Thirty five, postmenopausal women with two, repeated annual visits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…For example, Linkov et al have shown that CXCL9 (also known as monokine induced by gamma-interferon, MIG), but not CXCL10 (interferon-induced protein of 10 kDa, IP-10) had low reliability (intra-class correlation coefficient, ICC50.55) on repeated blood samples collected yearly from healthy women [23]. Serum measurements of chemokines may be easier to obtain than their expression in skin samples, especially when one intends to evaluate the effect of a given therapy, since at least two skin biopsies would have to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Linkov et al have shown that CXCL9 (also known as monokine induced by gamma-interferon, MIG), but not CXCL10 (interferon-induced protein of 10 kDa, IP-10) had low reliability (intra-class correlation coefficient, ICC50.55) on repeated blood samples collected yearly from healthy women [23]. Serum measurements of chemokines may be easier to obtain than their expression in skin samples, especially when one intends to evaluate the effect of a given therapy, since at least two skin biopsies would have to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Intra- and inter-assay variability of the assays ranged from 5-6% and 13-15%, respectively. Luminex technology has been shown to be a reliable tool for measuring large number of analytes in healthy individuals (25-27). …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, we developed panels of markers that showed significant potential to detect early cancers [26-28]. Furthermore, Luminex technology was shown to be a reliable tool for measuring large number of analytes in healthy individuals [29-31]. Thus, we wanted to expand the knowledge we accumulated in the area of cancer biomarkers to evaluate biomarker changes in healthy individuals who are at high risk for cancer development.…”
Section: Introductionmentioning
confidence: 99%